Pencarian Jalur Terdekat Pada Pemetaan Sekolah Dasar Dengan Algoritma A-Star (A*) Berbasis Web - Tambun, Jerisman Jhon Wesli; Herlawati, Herlawati; Atika, Prima Dina (Journal of Students‘ Research in Computer Science, 2022)
Elementary school is the starting place for a child to start education and get various kinds of experiences. Elementary school is the highest level of education compared to Junior High School and Senior High School. The large number of elementary schools makes parents/guardians not know for sure where the elementary school is located. This makes parents/guardians not have many references to send their children to school in the future. Based on the existing problems, the author proposes a web-based geographic information system that uses the A-Star Algorithm (A*) to be used as a means of information and also to add references to parents/guardians. The A-Star Algorithm (A*) is a method to search for information about the distance to reach the destination by selecting the closest route. The result of this research is a web-based geographic information system that can provide information about 6 samples of elementary schools along with the location and the closest route that can be passed in the Mustikajaya District area.